Foreign direct investment and the performance of Indonesian marketplace e-commerce corporation: An application of network, ownership, location, and internalisation framework - Kaukab, M. Elfan; Aryanto, Vincent Didiek Wiet (UUM Press, 2020)
Data on real-time marketing performance from micro, small and medium enterprises (MSMEs) selling their products in marketplace e-commerce corporations (MECCs) is a big challenge for researchers studying the performance of MECCs capital structure. This article explores the use of Google Trends to determine the impact of Foreign Direct Investment (FDI) on MECCs performance. The findings of the trend analysis are explained using the N-OLI framework. It is found that there was a sharp trend decrease in MECCs with partial FDI (Tokopedia and Bukalapak) and full domestic investment (Blibli). On the other hand, there was a sharp increase in MECCs full FDI (Shopee). Other MECCs with full FDI, namely Lazada, has experienced a decrease but it is not as consistent as that of partial FDI. An increase trend in Shopee has negative correlation with a decline trend in Bukalapak. However, after being grouped, partial FDI has a significantly higher mean score compared to full FDI, and MECCs without FDI has the lowest mean score. This finding shows that in the case of Indonesia, FDI plays a role in encouraging the success of MSMEs, especially in MECCs, which have a combination of FDI and domestic investment.